Fabrication of Human Skin Equivalents Using Decellularized Extracellular Matrix. Issue 3 (8th March 2022) - Sarmin, Atiya M.; Connelly, John T.
Abstract: There is a growing demand for in vitro models of human tissues that recapitulate the complex structures and functions found in vivo, and the biomaterials that support these physiologically relevant models are essential underpinning technologies. Here, we present an optimized protocol for generating human skin equivalents (HSEs) using a dermal matrix isolated from decellularized porcine skin. The decellularized extracellular matrix (dECM) contains a complex mixture of fibrillar collagens and matrisomal proteins that mimic native skin and can be produced in large quantities. The procedure for decellularization, digestion, and solubilization of the dECM is described in detail. In addition, we provide instructions for how to construct a three‐dimensional HSE model using the dECM as the dermal support matrix for human keratinocytes and dermal fibroblasts. Recent studies from our laboratory have shown that HSEs generated using porcine dECM display improved epidermal differentiation and stratification compared to existing protocols using type I collagen gels. Thus, dECM‐based biomaterials are a useful tool for replicating human skin physiology in vitro and developing advanced human skin models for therapeutic discovery and testing. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of decellularized extracellular matrix from porcine skin Basic Protocol 2 : Generation of human skin equivalents